Maternal Addiction to Parental Leave - Per Engström; Ann-Sofie Kolm; Che-Yuan Liang (Uppsala University, Department of Economics, 2006)
The increased demand for a more equal parental sharing of the responsibilities for children has led many countries to reconstruct their parental leave systems so to provide stronger incentives for fathers to participate in childcare. Fathers quotas are becoming widely spread across Europe. This paper provides arguments for why it may be welfare improving for both parents to increase the fathers share of the familys parental leave time. However, regulations in terms of fathers quotas may not be optimal since it fails to recognise potentially heterogenous preferences. Instead, self-commitment devices should be provided in order to prevent mothers from taking too large share of the familys leave time.
urn:nbn:se:uu:diva-18862
Keywords: D10; J13; J16; J22; 330; Parental leave; Hyperbolic discounting; Addiction; Elternzeit; Väter; Mütter; Quotenregulierung; Zeitpräferenz; Theorie